Eyelash trichomegaly: a systematic review of acquired and congenital aetiologies of lengthened lashes. (31st December 2021) - Hutchison, D. M.; Duffens, A.; Yale, K.; Park, A.; Cardenas, K.; Mesinkovska, N. A.
Abstract: Long eyelashes have been popularized and many commercially available products exist to achieve eyelash growth as a desired cosmetic effect. Eyelash trichomegaly may be induced by medications, procedures, or be related to medical conditions; however, the exact mechanisms that govern eyelash growth are not well elucidated. This study aims to identify and summarize aetiologies associated with eyelash trichomegaly. We report a systematic review of 148 clinical trials, prospective and retrospective studies, and case reports describing all evidence‐based potential aetiologies of eyelash trichomegaly obtained from the Medline/PubMed and Cochrane Library through January 2021. Inclusion criteria were defined as (i) human studies involving congenital and acquired diseases in which eyelash trichomegaly is a characteristic or (ii) assessment of trichomegaly as an adverse or desired effect of a medication or procedure. Exclusion criteria included: animal studies, articles not available in English, outcomes unrelated to eyelash trichomegaly, and secondary review articles. Pharmacologic agents associated with eyelash trichomegaly included prostaglandin analogues (15‐keto fluprostenol isopropyl ester, bimatoprost, latanoprost, and travoprost), epidermal growth factor receptor inhibitors (cetuximab, erlotinib, and panitumumab), interferon‐alpha, and calcineurin inhibitors (tacrolimus and cyclosporine). Surgical procedures of the eyelid, as well as allergic rhinitis, atopic dermatitis, HIV, ichthyosis vulgaris (IV), uveitis, and vernal keratoconjunctivitis were also associated with increased eyelash growth. Congenital disorders associated with lengthened eyelashes included Cantú syndrome, CHOPS syndrome, Coffin–Siris syndrome, congenital heart disease, Cornelia de Lange syndrome, Costello syndrome, familial trichomegaly, Floating Harbor syndrome, Hermansky–Pudlak syndrome, Kabuki–Makeup syndrome, KBG syndrome, Oliver–McFarlane syndrome, Rubinstein–Taybi syndrome, and Smith–Magenis syndrome. While the most common cause of eyelash trichomegaly is topical bimatoprost use, better understanding of pathways implicated in eyelash trichomegaly may lead to the discovery of additional medications to stimulate eyelash growth and create avenues for future therapeutic interventions.